General ability and specific cognitive functions are lower in children with epilepsy after perinatal ischemic stroke - Vaher, Ulvi; Männamaa, Mairi; Laugesaar, Rael; Ilves, Norman; Ilves, Nigul; Loorits, Dagmar; Kool, Pille; Ilves, Pilvi (Frontiers in Stroke, 2024)
Epilepsy develops in one third of children after perinatal stroke. Both epilepsy and stroke may be risk factors for impaired cognitive abilities. It is still unclear how the development of epilepsy is related to the cognitive profile of children with perinatal stroke. The aim of the study was to evaluate general and specific cognitive functions in children with epilepsy and in children without epilepsy after perinatal ischemic stroke. Methods: The study group consisted of 51 children with perinatal ischemic stroke confirmed by magnetic resonance imaging: 27 (53%) children with arterial ischemic stroke and 24 (47%) with periventricular venous infarction. Magnetic resonance imaging and electroencephalography were performed in all patients after the neonatal period. Epilepsy was diagnosed if the child had at least two unprovoked seizures occurring >24 h apart or one unprovoked seizure with high recurrence risk. Cognitive assessment was performed using the Kaufman Assessment Battery for Children, II edition, at the age of ≥7 years. General ability (Fluid Crystallized Index, Mental Processing Index, Nonverbal Index) and specific cognitive functions (sequential processing, simultaneous processing, learning, planning, knowledge) were evaluated. Results: At the median age of 19.3 years (interquartile range 14.0-22) at the time of the follow-up for epilepsy, epilepsy had developed in 14 (27.5%) patients and 37 (72.5%) patients were without epilepsy. All general cognitive ability scores were lower in children with epilepsy compared to children without epilepsy. Among specific cognitive functions simultaneous processing, planning and knowledge were lower in children with epilepsy compared to children without epilepsy: simultaneous processing mean [95% confidence interval (CI)]: 78.5 (69.8-87.2) versus 96.9 (90-103.9), p=0.0018; planning mean (95% CI): 82.5 (73-92) versus 96.2 (88.7-103.6), p=0.026; knowledge median (25th, 75th percentile): 80.5 (75, 87) versus 92 (84, 108), p=0.023. Conclusions: Children with epilepsy after perinatal ischemic stroke have lower general cognitive ability compared to children without epilepsy. The profile of the subscales indicates lower verbal abilities and executive functions in children with epilepsy. Children with poststroke epilepsy need targeted cognitive monitoring for early aimed rehabilitation and for establishment of an adapted learning environment.